2007
DOI: 10.1111/j.1365-2265.2007.02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Marked chromogranin A elevation in a patient with bilateral adrenal incidentalomas, and its rapid normalization after discontinuation of proton pump inhibitor therapy

Abstract: Fig. 1Changes in serum CgA after withdrawal and 1 day after reintroduction of PPI-therapy. The broader horizontal line represents the upper normal level (98·1 ng/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Similar findings were reported in subjects with bilateral adrenal incidentaloma in which persistently elevated CgA after adrenalectomy for phaeochromocytoma was normalized only following suspension of PPI [3]. Our report as well as others observations serve as a reminder to clinicians to pay great attention to confounding factors before pursuing invasive and costly procedures in suspected cases of NETs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar findings were reported in subjects with bilateral adrenal incidentaloma in which persistently elevated CgA after adrenalectomy for phaeochromocytoma was normalized only following suspension of PPI [3]. Our report as well as others observations serve as a reminder to clinicians to pay great attention to confounding factors before pursuing invasive and costly procedures in suspected cases of NETs.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, other nonmalignant endocrine conditions leading to hypergastrinemia were reported to cause increased serum CgA [7]. Interestingly, recent reports have suggested that chronic use and dose escalation of PPI correlates with increased level of both CgA and serum gastrin [3, 5]. Our patient was maintained on the same dose of PPI throughout the period of use yet; in the last 4 months there was an alarmingly marked elevation of CgA.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…As proton pump inhibitors raise ChA (15,16), the exclusion criteria entailed need for such treatment and a concurrent pheochromocytoma, because metoclopramide can trigger hypertensive crises in these patients, besides refusal of the patients to undergo AVS and/or adrenalectomy. Peripheral plasma ChA and urinary free catecholamines, normetanephrine, and metanephrine were systematically measured before AVS to exclude pheochromocytoma.…”
Section: Methodsmentioning
confidence: 99%